2016
DOI: 10.1016/j.jsxm.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to and Attitudes Regarding Transgender Education Among Urology Residents

Abstract: Introduction Transgender individuals are underserved within the health care system but might increasingly seek urologic care as insurers expand coverage for medical and surgical gender transition. Aim To evaluate urology residents' exposure to transgender patient care and their perceived importance of transgender surgical education. Methods Urology residents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 10 publications
1
37
1
Order By: Relevance
“…Likewise, the surgical community should attempt to uniformly support efforts to understand transgender patients' surgical needs and outcomes. 16 Approximately 70% of plastic surgery residents 17 and 77% of urology residents 18 endorse the necessity of specialty training opportunities in genderconfirming surgery. However, our findings showed that only 24% and 11% of plastic surgery and urology programs, respectively, offer structured curricular content.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the surgical community should attempt to uniformly support efforts to understand transgender patients' surgical needs and outcomes. 16 Approximately 70% of plastic surgery residents 17 and 77% of urology residents 18 endorse the necessity of specialty training opportunities in genderconfirming surgery. However, our findings showed that only 24% and 11% of plastic surgery and urology programs, respectively, offer structured curricular content.…”
Section: Discussionmentioning
confidence: 99%
“…[67][68][69][70] Providing education to medical students about gender dysphoria is associated with improved knowledge, attitudinal change and professionalism. 71 Like the cisgender population, transgender people experience health issues that are not related to gender at all; educating all health professionals about transgender people will improve the access of transgender people to the varied general health resources they may require.…”
Section: Discussionmentioning
confidence: 99%
“…Education on the care of sexual and gender minority patients has been found to be lacking not only in medical education and medical residency programs, but in predoctoral dental education. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] For this reason, many providers may be uncomfortable with the delivery of care to transgender people.…”
mentioning
confidence: 99%